Assessing the impact of property size on residential water use for selected neighbourhoods in Lilongwe, Malawi - Makwiza, Chikondi; Jacobs, Heinz Erasmus (Journal of water, sanitation, and hygiene for development, 2016)
Malawi has one of the highest urbanisation rates in Africa, with an urban housing approach that favours large residential plot sizes. The impact of plot size on residential water use was evaluated by examining water use records, obtained for the period between January 2009 and December 2014, for formal residential properties in the city of Lilongwe. Water use increased with plot size in line with other reported research, but the dataset contained a considerable proportion of large plots, which were also associated with higher residential water use than presented in similar studies. The findings of this study point to the need for collaboration between water managers and urban planners to promote increased access of urban water supplies by appropriately managing future residential plot sizes.